Updating 'Stories' on social media and its relationships to contextual age and narcissism: A tale of three platforms – WhatsApp, Instagram and Facebook. Issue 5 (May 2022) - Menon, Devadas
Abstract: This study extends the uses and gratifications research into the feature use of social media platforms by identifying the motives for updating 'Stories' on three social media platforms, i.e. WhatsApp, Instagram and Facebook. Using survey data from adults (N = 338), this research identified seven motivations (i.e. socially rewarding self-promotion, social sharing, social influence, disclosure, escape, entertainment, and trendy fashion ) for updating Stories on WhatsApp, Instagram and Facebook. Age and gender differences were identified in the motivations for updating Stories on the three platforms. Cross-platform analysis revealed significant differences in the motivations for updating Stories across the three platforms. Social influence and disclosure motives positively predicted the intensity of updating Stories on all three platforms. Socially rewarding self-promotion predicted the intensity of updating Stories on Instagram and Facebook. Social sharing positively predicted the intensity of updating Stories on WhatsApp and Instagram, and trendy fashion emerged as a positive predictor of story updates only on Instagram. Finally, an analysis of social and psychological predictors revealed that Interpersonal interaction and Social activity positively predicted the intensity of updating Stories across the three platforms. Narcissists also exhibited high intensity of updating Stories on WhatsApp, Instagram, and Facebook. Abstract : Social media Stories, Status update, Uses and gratifications, WhatsApp, Instagram, Facebook, Contextual age, Life position indicators, Narcissism.